READING INTEREST CHARACTER OF PROSPECTIVE ELEMENTARY SCHOOL TEACHERS AT UNIVERSITAS PENDIDIKAN INDONESIA - Asri Aditya Lestari; Atep Sujana; Wahyu Sopandi (Universitas Majalengka, 2024)
Reading interest is one of the fundamental skills in language and is a highly effective learning activity for acquiring knowledge and literacy. Reading literacy is an essential skill, particularly for prospective educators; however, many students experience challenges in cultivating a reading habit. This research aims to: (1) describe the reading interest conditions of prospective teacher students at Universitas Pendidikan Indonesia (UPI), (2) elucidate the supporting and inhibiting factors for prospective teacher students (PTS) at UPI in their reading activities. This study employs a quantitative approach with a survey design. The research subjects are UPI PGSD (Elementary School Teacher Education) students. Data collection methods include questionnaires, surveys, and interviews. Data analysis involves descriptive analysis, frequency distribution, and percentage calculation. The findings reveal that: (1) the overall reading interest of PTS is categorized as low, (2) students' activities on campus before class hours mainly involve waiting and chatting with friends; only a small portion of students utilize their free time to read books or visit the library. (3) PTS' preferred books are novels and fiction, while scientific texts are less favored due to unappealing design and layout, (4) the time spent on reading books by PTS is relatively short, with less than 1 hour daily, and some do not allocate any time for reading, except when there are assignments or exams, (5) the major inhibiting factors for PTS in reading are internal, indicated by low reading habits or preferences for other interests over reading.